The complement system in pregnant women with severe preeclampsia - A. S. Antonova; J. Kh. Khizroeva; I. S. Kalashnikova; M. V. Tretyakova; Yu. A. Popyonova; N. F. Kuneshko; L. S. Fatkullina (Акушерство, гинекология и репродукция)
Here, we discuss current theories regarding preeclampsia (PE) pathogenesis, a role of the complement system in PE onset and evaluate an impact of altered complement system on pregnancy outcomes and PE severity. The studies conducted in the field of preeclampsia have indeed raised numerous new scientific questions and hypotheses. One of the key questions is whether the complement system activation is the primary PE cause or just a consequence of one or more pathological processes linked to this syndrome.